Companion robots for older people: importance of user-centred design demonstrated through observations and focus groups comparing preferences of older people and roboticists in South West England. Issue 9 (26th September 2019) - Bradwell, Hannah Louise; Edwards, Katie Jane; Winnington, Rhona; Thill, Serge; Jones, Ray B
Abstract : Objective: Companion robots, such as Paro, may reduce agitation and depression for older people with dementia. However, contradictory research outcomes suggest robot design is not always optimal. While many researchers suggest user-centred design is important, there is little evidence on the difference this might make. Here, we aimed to assess its importance by comparing companion robot design perceptions between older people (end users) and roboticists (developers). Design: Older people and roboticists interacted with eight companion robots or alternatives at two separate events in groups of two to four people. Interactions were recorded, participants' comments and observations were transcribed, and content was analysed. Subsequently, each group participated in focus groups on perceptions of companion robot design. Discussions were recorded and transcribed, and content was analysed. Participants and settings: Seventeen older people (5 male, 12 female, ages 60–99) at a supported living retirement complex, and 18 roboticists (10 male, 8 female, ages 24–37) at a research centre away-day. Results: We found significant differences in design preferences between older people and roboticists. Older people desired soft, furry, interactive animals that were familiar and realistic, while unfamiliar forms were perceived as infantilising. By contrast, most roboticists eschewed familiar and realistic designs, thinking unfamiliar forms better suited older people. Older people also expressed desire for features not seen as important by developers. A large difference was seen in attitude towards ability to talk: 12/17 (71%) older people but only 2/18 (11%) roboticists requested speech. Older people responded positively towards life-simulation features, eye contact, robot personalisation and obeying commands, features undervalued by roboticists. These differences were reflected in preferred device, with 'Joy for All' cat chosen most often by older people, while roboticists most often chose Paro. Conclusion: The observed misalignment of opinion between end users and developers on desirable design features of companion robots demonstrates the need for user-centred design during development.